Delinquent behaviors in Southern Italy: A survey on adolescents perceptions - Martina Barbera; Nicolina Rosi; Concetta Grillo; Murat Yildirim; Gülçin Güler Oztekin; Simona Scimone; Gabriele Allegra; Amelia Rizzo (Advances in Medicine, Psychology, and Public Health)
Introduction: Numerous studies have examined the precursors and personal traits associated with deviant behavior, but little is known about normative attitudes. This study aimed to conduct an exploratory survey on the perception and moral beliefs about deviant behavior. Methods: We collected data from 100 students belonging to two high schools in Calabria, Southern Italy, to whom was administered a revised version of the Italian version of the International Self-Reported Delinquency (ISRD-3) questionnaire and a self-rating scale for the moral evaluation of deviant behavior. Results: In our sample, deviant adolescents were less than 5%. However, it was possible to collect attitudes by drawing graffiti, illegally downloading from the internet, making their own justice, and signaling the police car. It has also emerged as difficult to correctly conceptualize and categorize rights and duties. Conclusions: Our results, discussed in the light of the literature, provide to policy-mahers and researchers helpful information on the most prevalent attitudes among adolescents in Southern Italy.